Insulin resistance predicts brain amyloid deposition in late middle‐aged adults. Issue 5 (17th July 2014) - Willette, Auriel A.; Johnson, Sterling C.; Birdsill, Alex C.; Sager, Mark A.; Christian, Bradley; Baker, Laura D.; Craft, Suzanne; Oh, Jennifer; Statz, Eric; Hermann, Bruce P.; Jonaitis, Erin M.; Koscik, Rebecca L.; et al.
Abstract: Background: Insulin resistance (IR) increases Alzheimer's disease (AD) risk. IR is related to greater amyloid burden post‐mortem and increased deposition within areas affected by early AD. No studies have examined if IR is associated with an in vivo index of amyloid in the human brain in late middle‐aged participants at risk for AD. Methods: Asymptomatic, late middle‐aged adults (N = 186) from the Wisconsin Registry for Alzheimer's Prevention underwent [C‐11]Pittsburgh compound B (PiB) positron emission tomography. The cross‐sectional design tested the interaction between insulin resistance and glycemic status on PiB distribution volume ratio in three regions of interest (frontal, parietal, and temporal). Results: In participants with normoglycemia but not hyperglycemia, higher insulin resistance corresponded to higher PiB uptake in frontal and temporal areas, reflecting increased amyloid deposition. Conclusions: This is the first human study to demonstrate that insulin resistance may contribute to amyloid deposition in brain regions affected by AD.